Children’s Key Competencies: An Introduction to Its Theoretical Constructs, Impact, and Formation through the Comprehensive Practical Activity Curriculum - Xiang, Jing; Fu, Zaoxiu (International Dialogues on Education Journal, 2022)
The comprehensive practical activity curriculum can be said to be created to cater to children’s curiosity and nature of exploration. Through the creation of problem situations, children are guided not only to explore what the world is, but also to pay close attention to what the world will be and cultivate children’s key competencies in the real process of exploring and experiencing the world by following the behaviors of participation, reflection, service, protection and improvement of the world, such as humanistic connotation and scientific spirit, responsibility consciousness and feelings of family and country.